1999
DOI: 10.1001/archpedi.153.4.409
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Obesity via a School-Based Interdisciplinary Intervention Among Youth

Abstract: To evaluate the impact of a school-based health behavior intervention known as Planet Health on obesity among boys and girls in grades 6 to 8. Design: Randomized, controlled field trial with 5 intervention and 5 control schools. Outcomes were assessed using preintervention (fall 1995) and follow-up measures (spring 1997), including prevalence, incidence, and remission of obesity.Participants: A group of 1295 ethnically diverse grade 6 and 7 students from public schools in 4 Massachusetts communities.Interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
1,005
7
31

Year Published

2000
2000
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,147 publications
(1,070 citation statements)
references
References 71 publications
27
1,005
7
31
Order By: Relevance
“…50 Programs appear to have been enhanced when physical activity was not merely encouraged, but made a routine part of the school day. 45,51,53 Very few studies focusing on TV reduction were available at the time this review was conducted 52,55 and only one was amenable to computation of effect size. 55 This strategy remains appealing despite the relative paucity of data and deserves further attention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…50 Programs appear to have been enhanced when physical activity was not merely encouraged, but made a routine part of the school day. 45,51,53 Very few studies focusing on TV reduction were available at the time this review was conducted 52,55 and only one was amenable to computation of effect size. 55 This strategy remains appealing despite the relative paucity of data and deserves further attention.…”
Section: Discussionmentioning
confidence: 99%
“…Common strategies included: parent or family member participation; [37][38][39][40][41][42][43][44][45] changing the physical environment; 43,44,[46][47][48] [37][38][39] and student training in behavioral techniques such as self-monitoring. 38,39,52,53 Detailed descriptions of each study can be found in Table 1.…”
Section: Study Identificationmentioning
confidence: 99%
“…9 To reduce child overweight status, successful interventions have included limiting the amount of time spent in front of the television. [46][47][48][49][50] However, it is difficult to consistently monitor and limit TV viewing time over the long term. A simple and effective screen for child risk factors for overweight that could be employed by pediatricians and other health-care providers would be to ask if a child has a TV in his or her bedroom.…”
Section: Discussionmentioning
confidence: 99%
“…Several intervention studies have evaluated the impact of increased physical activity or decreased sedentary behavior as part of multifactorial interventions on prevention of weight/fatness gains or remission of overweight in clinical and community-based settings, with mixed results. [4][5][6][7][8][9] One small pilot study that focused only on decreasing sedentary behavior yielded significant results, 10 providing experimental evidence that sedentary behavior is causally linked to overweight. After briefly summarizing select cross-sectional studies, we review prospective research on the role of physical activity and inactivity in the development of obesity or increased relative weight, in children and adolescents, and highlight some of the methodological challenges and limitations in the literature to date.…”
Section: Introductionmentioning
confidence: 99%